PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN BEDAK WARDAH PADA MAHASISWI FAKULTAS EKONOMI DAN BISNIS UNIRAYA - Duha, Titin Dwiyantari (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The purpose of this study was to determine the influence of brand image on purchasing decisions. The type of research used is quantitative research. The source of the data is a student of the Faculty of Economics and Business UNIRAYA, with a sample of 73 people. The data collection technique used was a questionnaire that was distributed to all respondents. The data analysis technique used is simple regression analysis. From the results of this study it can be seen that the value of t_(calculate) is 6.288 > t_(table) is 1.667 at a significant level of 0.000<0.05. And through the test coefficient of determination (R2) of 0.358 (35.8%), which means that 35.8% of the diversity of Purchase Decision variables can be explained by the Brang Image variable while the remaining 64.2% is influenced by other variables not mentioned in this study. The results of this study show that brand image variables have a positive and significant effect on purchasing decisions.